An Analysis of Sharia Economic Practices in Pekalongan from Habib Luthfi’s Perspective - Surur, Achmad Tubagus; Adinugraha, Hendri Hermawan; Achmad, Dliyauddin (Yayasan Abdurrauf Cendekia Nusantara, 2025)
Abstract: This study analyzes the implementation of Sharia economic practices in Pekalongan from the perspective of Habib Muhammad Luthfi bin Yahya, a prominent Islamic scholar and spiritual leader in Indonesia. The research aims to explore how Habib Luthfi’s thoughts and teachings influence the ethical, spiritual, and practical dimensions of the local Sharia economy. Employing a qualitative method with a library research approach, this study examines various written and recorded sources, including Habib Luthfi’s speeches, Sharia economic literature, and previous scholarly works. The analysis employs content analysis and hermeneutic interpretation to uncover the underlying values, principles, and socio-religious context that shape Habib Luthfi’s economic thought. The findings reveal that his perspective emphasizes moral integrity, justice, and communal welfare as the foundation of economic activities. His approach integrates Sufistic ethics with Sharia economic principles, promoting an inclusive and spiritually grounded economic system. Moreover, his leadership fosters community-based empowerment through cooperation, honesty, and social solidarity. The study concludes that Habib Luthfi’s perspective provides a significant model for developing a Sharia-based economic framework rooted in spirituality, cultural values, and national identity. This research contributes to the theoretical understanding of Sharia economics and offers practical insights for strengthening Sharia economic practices in Indonesia. Abstrak: Penelitian ini menganalisis implementasi praktik ekonomi syariah di Pekalongan dari perspektif Habib Muhammad Luthfi bin Yahya, seorang ulama Islam dan pemimpin spiritual terkemuka di Indonesia. Penelitian ini bertujuan untuk mengeksplorasi bagaimana pemikiran dan ajaran Habib Luthfi mempengaruhi dimensi etis, spiritual, dan praktis dari ekonomi syariah lokal. Menggunakan metode kualitatif dengan pendekatan penelitian perpustakaan, studi ini menganalisis berbagai sumber tertulis dan tercatat, termasuk pidato-pidato Habib Luthfi, literatur ekonomi Syariah, dan karya-karya ilmiah sebelumnya. Analisis menggunakan analisis konten dan interpretasi hermeneutik untuk mengungkap nilai-nilai, prinsip-prinsip, dan kajian sosial-religius yang membentuk pemikiran ekonomi Habib Luthfi. Temuan menunjukkan bahwa perspektifnya menekankan integritas moral, keadilan, dan kesejahteraan komunitas sebagai landasan aktivitas ekonomi. Pendekatannya menggabungkan etika Sufi dengan prinsip-prinsip ekonomi Syariah, mempromosikan sistem ekonomi yang inklusif dan berlandaskan spiritualitas. Selain itu, kepemimpinannya mendorong pemberdayaan berbasis komunitas melalui kerja sama, kejujuran, dan solidaritas sosial. Studi ini menyimpulkan bahwa perspektif Habib Luthfi menyediakan model yang signifikan untuk mengembangkan kerangka kerja ekonomi berbasis Syariah yang berakar pada spiritualitas, nilai-nilai budaya, dan identitas nasional. Penelitian ini berkontribusi pada pemahaman teoretis tentang ekonomi Syariah dan menawarkan wawasan praktis untuk memperkuat praktik ekonomi Syariah di Indonesia.